State regulatory principals and local bureaucratic agents: the politics of local solid waste management - Rasmussen, Thomas H. (2000)
Regulatory agencies often delegate responsibility for implementing policy to agencies at lower levels of government. This article models strategic bargaining between New York State regulatory principals at the Department of Environmental Conservation (DEC) and county landfill agents as an iterated prisoner's dilemma game. Data are drawn from regional DEC and county records over a 7-year period. Local regulatory agents balance local political pressures, career aspirations, and the probability of being caught and punished in deciding whether to cooperate or defect with regional DEC regulators. Regional DEC regulatory principals balance their support from governor and legislature, the importance of the regulatory issue, and the constraints of scarce resources in deciding whether to cooperate or defect with local landfill operators. - Reproduced
Keywords: Wastes